Sexual and reproductive health services for women with disability: a qualitative study with service providers in the Philippines. Issue 1 (December 2015) - Lee, Kira; Devine, Alexandra; Marco, Ma.; Zayas, Jerome; Gill-Atkinson, Liz; Vaughan, Cathy
Abstract Background The Philippines has ratified the United Nations Convention on the Rights of Persons with Disabilities and recently passed domestic legislation protecting the sexual and reproductive rights of people with disability. However women in the Philippines continue to report barriers to sexual and reproductive health services, and there is limited empirical evidence available to inform policy makers' efforts to respond. This study aims to contribute to the available evidence by examining service providers' perceptions of disability and their experiences providing sexual and reproductive health services to women with disability. Methods The study was conducted as part of a larger three-year program of participatory action research that aims to improve the sexual and reproductive health of women with disabilities in the Philippines. Fourteen in-depth interviews and two focus group discussions were conducted with a total of thirty-two sexual and reproductive health service providers in Quezon City and Ligao. Qualitative data were analysed to identify key themes in participants' discussion of service provision to women with disability. Results Analysis of service providers' accounts suggests a range of factors undermine provision of high quality sexual and reproductive health services to women with disability. Service providers often have limited awareness of the sexual and reproductive health needs of women with disability and inadequate understanding of their rights. Service providers have had very little training in relation to disability, and limited access to the resources that would enable them to provide a disability inclusive service. Some service providers hold prejudiced attitudes towards women with disability seeking sexual and reproductive health services, resulting in disability-based discrimination. Service providers are also often unaware of specific factors undermining the health of women with disability, such as violence and abuse. Conclusion Recent legislative change in the Philippines opens a window of opportunity to strengthen sexual and reproductive health service provision across the country. However the development of services that are disability-inclusive will require substantial efforts to address supply-side barriers such as prejudiced service provider attitudes and limited capacity. Disability inclusion must be prioritised for the national goal of responsible parenthood and reproductive health to be realised for all.